PENERAPAN LEX SPECIALIS DEROGAT LEGI GENERALI DALAM HARMONISASI UU IKN DAN UU AGRARIA - Kurnia, Ida; Louis Sebastian Anot Putra; Kasmita Andriani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
This article examines the management of Indonesia's natural resources based on Article 33 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) and the Basic Agrarian Law (UUPA), as well as its impact on indigenous land rights in the development of the Nusantara Capital City (IKN). The state has the authority to control natural resources for the welfare of the people, as regulated by the UUPA, particularly Article 4 Paragraph (1) on land control rights. The UUPA was formulated to eliminate the dualism between colonial agrarian law and customary law and to provide legal certainty regarding land rights. With the enactment of Law No. 3 of 2022 on IKN, new challenges have emerged in managing land in Kalimantan, particularly regarding indigenous territories, which encompass 476 mapped areas with vast customary forests. The main implication of this policy is the potential for conflicts between indigenous communities and the government concerning land control. The author employs a qualitative research method, using a legal and customary law approach, to explore the issue of how to protect indigenous rights and prevent their marginalization in large-scale development projects. On the other hand, opportunities arise to create more inclusive and sustainable policies by ensuring that local interests are considered in the development of IKN. This article highlights the importance of harmonizing the 1945 Constitution, UUPA, and IKN Law to balance the needs of national development and the protection of indigenous rights, thereby reducing the potential for regional conflicts and increasing legal certainty for investors.